The Attitudes of Jordanian School Students towards M-Learning in Math: An Empirical Study - Al-Alawneh, Abdullah Mostafa (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to explore the attitudes of Jordanian school students towards M-learning in math. A descriptive analytical approach was adopted and a five point Likert questionnaire was developed. A purposive sample was selected from Omar bin Al-Khatab School for Boys in Amman, Jordan. It consists from 52 9th grade male students. The questionnaire forms were distributed to all the students. All the forms were retrieved and considered valid for statistical analysis. SPSS was used. It was found that Jordanian school students have positive attitudes towards M-learning in math. It was found that most of the respondents use mobile for academic goals. It was found that M-learning in math raises students’ academic achievement in math course and motivates them to learn math. However, M-learning in math doesn’t participate in improving students’ communication skills. The researcher recommends setting policies by the Jordanian Ministry of Education for encouraging teachers and students to practice m-learning.